Male Reproductive Strategies in Black and Gold Howler Monkeys (Alouatta caraya) - Oklander, Luciana Inés (2014)
Behavioral and demographic factors such as group size, social structure, dispersal patterns, and mating systems affect male reproductive success. In the present study, we analyze the relationship between social structure, genetic relatedness of adult males and offspring paternity in one population of Alouatta caraya inhabiting a continuous forest in Northern Argentina. After 14 months of behavioral studies and genotyping 11 microsatellites, we found that dominant or central males achieved greater mating success and fathered all the offspring conceived during our study in two multimale?multifemale groups (both including three adult males). Although skewed toward the dominant males, females copulated with almost all resident males and with extra group males. We found significantly fewer agonistic interactions between adult males in the group with fewer females and where males were more genetically related to each other (average relatedness R-0.237; 0.015 int/ind/hr vs. r-0.02; 0.029 int/ ind/hr). Paternity was also analyzed in two other neighboring groups which also showed strong skew to one male over a 2 year period. These results reveal that even though female black and gold howlers mate with many males, infants are typically fathered by one dominant male. Am. J. Primatol. 76:43-55, 2014.